Preventing and Reducing Coercive Measures—An Evaluation of the Implementation of the Safewards Model in Two Locked Wards in Germany - Baumgardt, Johanna; Jäckel, Dorothea; Helber-Böhlen, Heike; Stiehm, Nicole; Morgenstern, Karin; Voigt, Andre; Schöppe, Enrico; Mc Cutcheon, Ann-Kathrin; Velasquez Lecca, Edwin Emilio; Löhr, Michael; Schulz, Michael; Bechdolf, Andreas; et al. (Frontiers in Psychiatry, 2019)
IIntroduction Aggression and violence are highly complex problems in acute psychiatry that often lead to the coercive interventions. The Safewards Model is an evidence-informed conflict-reduction strategy to prevent and reduce such incidents. The aim of this study was to evaluate the implementation of this model with regards to coercive interventions in inpatient care. Materials and Method We evaluated outcomes of the implementation of the Safewards Model in two locked psychiatric wards in Germany. Frequency and duration of coercive interventions applied during a period of ten weeks before and ten weeks after the implementation period were assessed through routine data. Fidelity to the Safewards Model was assessed by the Organization Fidelity Checklist. Results Fidelity to the Safewards Model was high in both wards. The overall use of coercive measures differed significantly between wards (case-wise: χ2 (1, n = 250) = 35.34, p ≤ 0.001; patient-wise: χ2 (1, n = 103) = 21.45, p ≤ 0.001) and decreased post implementation. In one ward, the number of patients exposed to coercive interventions in relation to the overall number of admissions decreased significantly (χ2 (1, 182) = 9.30, p = 0.003). Furthermore, the mean duration of coercive interventions overall declined significantly (U(55,21) = -2.142, p = 0.032) with an effect size of Cohen’s d = -0.282 (95% CI: -0.787, 0.222) in that ward. Both aspects declined as well in the other ward, but not significantly. Discussion Results indicate that the implementation of the Safewards interventions according to the model in acute psychiatric care can reduce coercive measures. They also show the role of enabling factors as well as of obstacles for the implementation process.